Geology and geochemistry of the rocks of Ushiri Valley, District Dir, Northern Pakistan - Shah, Mohammad Tahir; Ihtisham-Ul-Haq; Hamidullah, Syed (Journal of Himalayan Earth Sciences, 2000)
The study area is lying in the north-western portion of the Kohistan arc terrane. This terrane is bounded by two suture zones of regional extent at its northern and southern sides, believed to be formed by obliteration of ancient oceanic basin. This arc experienced its first collision at its northern margin with the Karakorum plate at 90-80 Ma, and its second collision at the southern margin during Early Eocene with the Indian plate. Rocks of the study area are distinguished into two main lithological units: (1) Amphibolites and (2) Metadiorites/metagranodiorites. The amphibolites occupy the southern part of the studied area while metadiorite/metagranodiorites are exposed in the northern part of the study area. Both these rock units have intrusive contacts and exhibit local faulting and shearing. The amphibolites also host small patches of slightly metamorphosed gabbro-norites. The amphibolites are generally massive but also exhibit banding at places. They are intruded by quartz and quartzo-feldspathic veins especially in areas where shearing and faulting are intense. They are also intruded by the metadiorite / metagranodiorite in the form of small plugs. The metadiorites / granodiorites are medium to coarse-grained, massive in character and have xenoliths of amphibolites. Copper mineralization in the form of disseminated grains of tetrahydrite and chalcopyrite and supergene enrichment in the form of malachite and azurite occur within quartz veins in limited areas. Amphibolites are mainly composed of hornblende and plagioclase with subordinate amount of quartz and alkali feldspar. Biotite, muscovite, chlorite, epidote, apatite, sphene, rutile, calcite and opaque occur as accessories. The metagabbro-norites contain plagioclase, orthopyroxene and clinopyroxene as the dominant mineral constituents. The metadiorite, quartz-diorite and metagranodiorite are dominantly composed of plagioclase with variable proportion of quartz and alkali feldspar. The other minor constituents include biotite, hornblende, muscovite, apatite, sphene, zircon, garnet and opaque. Chemically the amphibolites and metagabbro-norites are comagmatic. Their chemical characteristics favor the igneous parentage (i.e., host gabbro-norite) for the studied amphibolites. The major and trace elements study of these rocks suggests that these are of calc-alkaline nature and are formed by the arc magma within the subduction related environment. The chemical characteristics of the granitoid rocks (metadiorite/metagranodiorite) suggest that these are co-magmatic and have close affinity towards the calcalkaline rocks, developed in island arc type of set up. Both the amphibolites and gabbro-norites could be related to either Kamila amphibolites belt or Chilas Complex. The studied granitoids are, however, correlated with the stage Il pluton of the Kohistan batholith.